Buying well‐being: Spending behavior and happiness. Issue 5 (6th April 2018) - Aknin, Lara B.; Wiwad, Dylan; Hanniball, Katherine B.
Abstract: The relationship between money and happiness is complex. While a large literature demonstrates a small but significant positive association between overall income and well‐being, a relatively new area of research explores the emotional consequences of everyday spending choices. Here we review this recent but rapidly growing area of investigation. We begin by briefly summarizing the link between money and happiness. Then, through the lens of 2 dominant models of human happiness, we suggest that seemingly inconsequential spending choices may provide an underappreciated and underutilized route to greater well‐being. Finally, we review new empirical evidence demonstrating that individuals can use their disposable income to increase their happiness by investing in experiential (rather than material) purchases, more free time, routine, self‐expression, and generosity.